ANALISA LAPORAN KEUANGAN DALAM EFEKTIVITAS PENILAIAN PERMOHONAN KREDIT - Kumalasari, Nety; Julianti, Niluh Tiara (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
The purpose of this study is to ascertain how well Bank Mayapada Wayhalim Functional Office evaluates credit applications by examining financial statements. In this study, quantitative methods are combined with descriptive research methods. The financial reports of bank customers from 2020 to 2022 that were gathered from bank paperwork make up the processed data. By conducting credit checks on potential borrowers and determining the curent ratlo, quiick ratlo, debt to equityy ratlo, debt to asset ratlo, proflt margln, return onn assets, and return ln equlty, anaIysis of flnancial statements was successful in improving bank effectiveness in managing liquidity, solvency, and profitability.